Gamma irradiation synthesis and influence the optical and thermal properties of cadmium sulfide (CdS)/poly (Vinyl pyrolidone) nanocomposites - Gasaymeh, Shawkat Salameh; Radiman, Shahidan; Lee, Yook Heng; Saion, Elias (Science Publications, 2010)
Problem statement: Gamma irradiation has been successfully used to prepare a spherical cadmium sulfide CdS/Poly Vinylpyrolidone (PVP) quantum dots nanoparticles with enhancement of their optical band gap energy and thermal properties at room temperature and under ambient pressure. Sodium thiosulfate was used as a sulfur source in an aqueous solution. The formation of lower band gap energy of CdS/PVP nanoparticles and thermal stability can be controlled by using different irradiation doses. TEM images showed that the CdS/PVP particle size tends to be smaller and with better distribution as irradiation dose increases. Approach: Gamma (Î³) irradiation offered many advantages for the preparation of metal nanoparticles by producing large number of hydrated electrons during Î³-ray irradiation, which can reduce the metal ions to zero valiant metal particles. Results: CdS/PVP nanoparticles were successfully prepared in one-step by Î³-irradiation technique in an aqueous system at room temperature and under ambient pressure. The particle size was found to be less than 10 nm based on the Transmission Electron Microscopy (TEM) that depended on the irradiation doses value, which showed a well distribution with a controlled size as doses change. The presence of PVP polymer was considered an important reason that influenced the shape and the distribution of those nanoparticles. The optical band gap energy of those nanoparticles was calculated by using the UV-VIS absorption spectra. Thermal analysis TGA showed that the composite had a higher degradation temperature than the PVP alone. A possible mechanism of the formation of cadmium sulfide by irradiation system was proposed. Conclusion: This result indicated that CdSO4 can effectively dope PVP and enhance the optical and thermal properties. In addition, Î³-irradiation is an effective technique for preparing inorganic/organic nanocomposites.